Report on Fiscal Safeguards Pilots. (Policy Papers; Policy Paper ;, 2013)
This paper reports on the results of a pilot exercise on fiscal safeguards conducted by the Fiscal Affairs Department (FAD) during FY2013. The exercise was launched following an independent review of the existing safeguards policy in 2010 in which many Directors encouraged staff to highlight fiscal safeguards risks in cases where a substantial portion of the resources provided by the Fund for balance of payments support is channeled to state treasuries for budget purposes. Pilot fiscal safeguards exercises were conducted for five countries: Antigua and Barbuda, Cyprus, Greece, Ireland, and Kyrgyz Republic.